Extractive Spectrophotometric Determination of Malathion in Environmental Samples Using Gention Violet - K. M. Reddy; K. Suvardhan; K. Suresh Kumar; D. Rekha; P. Chiranjeevi (E-Journal of Chemistry)
A new simple and selective spectrophotometric method is developed for the determination of malathion by using Gention violet is described. The method was based on the alkaline hydrolysis of malathion in presence of sodium ethoxide to form sodium dimethyl dithiophosphate (Na-DMDTP). The Na-DMDTP was formed as an ion-pair complex with cationic dye, gention violet. The ion-pair complex was extracted into chloroform. The color of the organic layer was measured at 587 nm. The method was applied to the determination of malathion residues in water, grain and soil samples